Manajemen Risiko Teknologi Informasi Pada Penerapan E-Recruitment Berbasis ISO 31000:2018 Dengan FMEA (Studi Kasus PT Pertamina) - Pribadi, Hanafi Indra; Ernastuti, Ernastuti (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
Increasing the efficiency of time and human resources in the process of recruiting PT. Pertamina (Persero) to carry out its business processes that are spread throughout Indonesia is very much needed by implementing a website-based online recruitment system. Increased efficiency is obtained from a system that runs without constraints, while the weaknesses (vulnerabilities) in a system will cause great threats to the company, then the risk management of information technology on the application of the E-Recruitment system needs to be done by referring to ISO 31000: 2018 and risk assessment to get a Risk Priority Number (RPN), which is the priority of risk treatment for each risk attribute using the FMEA (Failure Modes and Effects Analysis) method based on ISO 31010: 2009 with the aim of knowing and assessing how much the threats and risks in an information system can become consideration of company stakeholders in implementing the system. Risks obtained in this study are 3 types of potential risks and 28 risk attributes, after a risk assessment has been obtained, the results are obtained that 7 risk attributes require special attention in the process of implementing the system so that it can run well in the future.